The Influence of Pet Plastic Waste Gradations as Coarse Aggregate Towards Compressive Strength of Light Concrete. (2017) - Nursyamsi,; Zebua, Winner Syukur Berkat
Abstract: In recent years, the use of substitute materials of concrete aggregate such as industrial wastes and other aggregates, which are light, is being a concern. It is due to these materials can be a solution in order to manage wastes from industry and also to reduce the weight of building structures. This study utilizes Poly Ethylene Terephthalate (PET) plastic waste which is light as coarse aggregates. The coarse aggregate from PET plastic waste is the result of the PET-heated to produce agglomeration, and then it is cooled and crushed into aggregates that have variety of sizes with certain gradations. The purpose of this study is to determine the compressive strength of light concrete of PET plastic waste as coarse aggregate and the influence of aggregate gradations towards the compressive strength of concrete that is produced. The material testing with various fineness modulus (FM) produces various results. The maximum compressive strength is achieved on sample using the maximum fineness modulus of PET plastic waste aggregate. According to SNI 03-3994-2002, the weight and compressive strength of the material should fit the standard. As the result, the gradation of coarse aggregate of PET plastic waste can affect the compressive strength of light concrete.